Outcome of Triplet Pregnancy with Concurrent Uterine Myoma: Successful Management of a Rare Case - Mirza Aditya Hakim; Syahrul Rauf; Iin Fadhilah Utami Tamasse (Universitas Negeri Gorontalo, 2026)
The management of a triplet pregnancy complicated by a degenerating fibroid is reported. The patient presented with persistent abdominal pain radiating to the back and a watery vaginal discharge mixed with mucus and blood. She had no relevant medical, family, or medication history and had not received tetanus immunization during pregnancy. Examination revealed stable vital signs, a fundal height of 39 cm, and a monochorionic triamniotic triplet pregnancy with all three fetuses in cephalic presentation and normal heart rates. Vaginal examination showed 1 cm cervical dilation with intact membranes and a bloody vaginal discharge. The patient was diagnosed with a triplet pregnancy in latent labour, complicated by a large fibroid. A caesarean section was performed for delivery, followed by myomectomy and subsequent intrauterine device (IUD) insertion. The removed mass showed necrotic and hemorrhagic tissue. Histopathology confirmed a leiomyoma with cystic and red degeneration. The mother and her three babies were in good health after the operation and at the three‑month follow‑up. In conclusion, caesarean section combined with myomectomy can be safely performed in selected cases of triplet pregnancy with large fibroids, particularly when the mother and fetus are clinically stable.Keywords: Cesarean section, high-risk pregnancy, myomectomy, triplet pregnancy, uterine fibroid